Recent Trend in Antibiotic Resistance Pattern of Methicillin-Resistant Staphylococci from Animal and Huma - Ghadosare, SN; Purohit, JH; Patel, JS; Mathapati, BS; Javia, BB; Barad, DB; Sindhi, SH (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The aim of this study was to evaluate the antibiotic resistance pattern of Methicillin-Resistant Staphylococci (MRS) isolated from animals and human beings. During the study, total 9 MRS isolates from 86 Staphylococcus spp. and 20 MRS isolates from 62 Staphylococcus spp. were identified from 202 animal and 100 human samples, respectively. All the MRS isolates from animals showed higher susceptibility to amikacin and rifampicin (100%) followed by oxytetracyclin (77.78%) and chloramphenicol (66.66%). Similarly, the MRS isolates from human showed higher susceptibility to methicillin (98%) followed by rifampicin and gentamicin (90% each), chloramphenicol (80%) and ofloxacin and levofloxacin (70% each). The higher rates of methicillin, gentamicin, ofloxacin and levofloxacin sensitivity were observed in human beings as compared to animal MRS isolates, whereas higher rates of amikacin, rifampicin and oxytetracyclin sensitivity were observed in animal isolates as compared to human MRS isolates. The MIC level of all the MRS isolates from both the species were recorded and found 89.67% correlation of phenotypic oxacillin susceptibility test with mecA gene PCR amplification among MRS isolates from animal and human. mastitic dairy animals (Hendriksen et al., 2008). Staphylococcus aureus can cause a wide spectrum of diseases in both humans and animals. An important public health issue concerning staphylococcal infections is the development of drug resistance due to the intensive use of antimicrobials in human and veterinary medicine (Shanehbandi et al., 2014). The virulence factors are crucial to establish the infection and cause pathogenesis for S. aureus. The emergence of antibiotic-resistance has been shown in S. aureus